Nutritional status of the pre-school children in UHTC area of Santhiram Medical College, Nandyal, Kurnool district - Ebenezer, B. S. Isaac; Sushma, Marupuri; Pasha, M. A. Mushtaq; Fatima, Afsar; Veereshappa, D. K. (International Journal Of Community Medicine And Public Health, 2018)
Background: Malnutrition is one of the major problems in the world which suffers middle income countries in the world, malnutrition is mainly of two types over weight and underweight, the present topic is concerned to the underweight of the children among the age group between 3 yrs to 6 yrs. The aims and objectives of the study were to assess the nutritional status of children among 3-6 yrs in UHTC area of SRMC Nandyal and to identify the influence of education, occupation, and socio economic status on the nutritional status of preschool children. Methods: Community based on cross sectional study. Sampling method used is 4pq/l2. Sample size was 210. Results: Total numbers of participants in the study are 210 members. 58% are males and 42.4% are females. Among the participants 42.4% fathers and 53.8% mothers are illiterates who occupy the majority. In occupation majority of the fathers and mothers are working as unskilled labour i.e. 61.4% and 53.3%. Among the participants majority of them belong to class IV i.e. 48.6%. When we see the grading of malnutrition 51% of them are moderately malnourished. Significance difference has been observed among the educational status of the mother and the nutritional status of the baby. Conclusions: In the present study most the children malnourished are boys. Education of mother played major role in degree of malnutrition higher the educational status lower the malnutrition.